2011
DOI: 10.1002/cncr.26127
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of neurocognitive function after treatment for central nervous system germ cell tumors in childhood

Abstract: BACKGROUND: Central nervous system germ cell tumors (CNS GCT) are typically localized to midline structures of the brain, including the pineal and suprasellar/pituitary regions. Management of these tumors depends on underlying histology (germinoma or nongerminomatous germ cell tumor). Knowledge about neurocognitive outcome in these patients is limited. Longitudinal neurocognitive outcome in CNS GCT patients seen for neuropsychological evaluation at a single institution was explored. METHODS: Thirty‐five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 38 publications
6
66
0
Order By: Relevance
“…Neurologically, the frontal lobes and their connections throughout the brain, including white matter tracts/integrity, are of integral importance to executive function. Not surprisingly, survivors of pediatric cancer have been found to be at risk for impaired executive functions, including both higher- and lower-level skills (Campbell et al, 2009; Conklin, Krull et al, 2012; Jansen, Miaskowski, Dodd, Dowling, & Kramer, 2005; Mabbott et al, 2011; Schatz et al, 2000). …”
mentioning
confidence: 99%
“…Neurologically, the frontal lobes and their connections throughout the brain, including white matter tracts/integrity, are of integral importance to executive function. Not surprisingly, survivors of pediatric cancer have been found to be at risk for impaired executive functions, including both higher- and lower-level skills (Campbell et al, 2009; Conklin, Krull et al, 2012; Jansen, Miaskowski, Dodd, Dowling, & Kramer, 2005; Mabbott et al, 2011; Schatz et al, 2000). …”
mentioning
confidence: 99%
“…31,39,40 Reductions in neurocognitive performance have been documented following administration of intrathecal chemotherapy in children with leukemia. 32 Given that the drug penetrates only a thin layer adjacent to the ventricular system, this suggests that periventricular cells may play an important role in neurocognitive function.…”
Section: Radiation Sparing Of the Npc Niches May Preserve Neurocognitmentioning
confidence: 99%
“…32 Given that the drug penetrates only a thin layer adjacent to the ventricular system, this suggests that periventricular cells may play an important role in neurocognitive function. However, improved neurocognitive performance in patients with central nervous system germ cell tumors who were treated with whole-ventricle radiation when compared with craniospinal radiation has been reported, 40 suggesting that perhaps the cells lining the ventricle may not be as vital as other areas in the brain in neurocognitive sequelae of RT. In addition, only 1 animal study to date has documented a relationship between RT dose to the SVZ and performance on neuropsychological testing, 41 and no human studies have confirmed this relationship.…”
Section: Radiation Sparing Of the Npc Niches May Preserve Neurocognitmentioning
confidence: 99%
“…Patients treated with ventricular versus craniospinal radiation displayed better outcome. The data are, however, difficult to interpret as there was an imbalance between dose prescriptions and treatment volumes according to histological subtype [70]. Only one series investigated neurocognitive function after the present treatment strategy consisting of chemotherapy followed by reduced dose whole ventricular irradiation.…”
Section: Neurocognitive Functionmentioning
confidence: 98%
“…Data on quality of survival and neurocognitive function are retrospective in nature, based on heterogeneous cohorts of patients including non-germinoma who received more intensive treatments [13,15,19,22,36,42,63,65,67,68,70,71]. Longitudinal observations are often missing and the instruments used considerably vary between series.…”
Section: Expert Commentarymentioning
confidence: 99%